Reinhart Koselleck’s Personal Sluices of Memory and Sediments of Experience - Nowak, Andrzej (Kwartalnik Historyczny, 2024)
The article analyses selected aspects of the biography of Reinhart Koselleck (1923–2006), a German historian and theoretician of history. In particular, it brings to the fore significant traces of the Second World War experiences of the author of Kritik und Krise. Further, it looks at their influence on Koselleck’s critical approach to the concept of collective memory and on the anti-utopian thrust of his historical theory.